(untitled) (Proceedings of Faculty of Civil Engineering, 2023)
The paper discusses the concept of traffic flow described by hyperbolic differential equations. In this paper the Lighthill-Whitham-Richards model (LWR model) is used to describe traffic flow. The said model uses two parameters to describe the traffic flow – density and average speed of vehicles. Numerical approximation of the LWR model is formulated through scalar conservation laws. The finite volume method is used for numerical results. The term of shock wave and propagation of rarefaction wave in traffic flow are described. This paper focuses on numerical simulation of traffic flow via fluid dynamics model for a single road with a traffic light. The results obtained in this paper are compared with previous studies.